Feminist Companion to Exodus to Deuteronomy - Brenner, Athalya (Feminist Companion to the Bible, 1994)
This volume is part of a series which provides a fundamental resource for feminist biblical scholarship, containing a comprehensive selection of essays, both reprinted and specially written for the series, by leading feminist scholars. The essays in this volume deal with social status and female sexuality, the textual figure of 'the daughter' and the character of Miriam. 'An enterprising series of collections of important and pioneering studies... Those teaching feminist courses will find the books invaluable as a resource for students' (C.S. Rodd, Expository Times).